Employer brand attractiveness: the effect of demographic variables on career goals - Gugup Kismono; Niken Lulanti Rahayu (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2021)
Purpose: This research aimed to observe the differences between respondents’ characteristics based on their career goals as part of employer brand, and to identify effective employer branding. It was important since many businesses failed to attract the best talent due to limited knowledge on organizational attractiveness and employer branding strategy.Design/methodology/approach: The data were collected through self-administered questionnaire. There were 16 items used to represent career goals attributes in employer branding. The data was ordered based on the characteristics’ relative importance and assigned points accordingly (the first rank is scored the highest = 6) and analyzed using a K-related samples test and weighted-mean average computation with ANOVA tables. K-independent samples and a One-Way ANOVA test to identify the differences of career goals preferences.Findings: Results showed that there were various significant different across respondents’ characteristics such as gender, marital status, academic achievement, work experience, and economic background. The differences between each group for the most and the least important career goals can still be observed. The findings for career goals items are generally consistent with the known theories of organizational attraction.Research limitation/implications: The data were collected from business school students. It is limited in that it may not have captured the reflections of potential employees groups in Indonesia whose characteristics combinations of experience and attitudes toward employer brand differed from the sample used. Applying these research findings should be done meticulously.Practical implications: This research offered an interesting insight on the relations of employer brand's attractiveness dimensions, career goals, and individual differences. Based on this research findings, organizations may consider emphasizing on the attributes that are attractive to high-achievers or to one specific gender.Originality/value: This research contributed to identifying how respondents perceive the dimensions ranking of employer brand attractiveness and analyzing the detail characteristics attractiveness (career goals) based on demographic variables.